A study of the calorific power of corncob briquettes, using residual oils as binders - Danielle Jaguaribe; Joelma Ferreira; Erika Santana; Anderson Silva (Academia Green Energy)
Corncob briquettes represent a promising new source of renewable energy. However, no concrete data on the calorific value of these briquettes currently exists in the literature. Representative samples of corncobs were therefore collected and then analyzed in the laboratory to determine the properties of this biomass, including moisture and density. The production of biomass briquettes followed standardized procedures, such as the reduction of moisture content and granulometric separation, and appropriate compaction techniques, with a hydraulic press under pressure of 7 kg/cm2 with a working range of 130–145°C. The analysis was carried out according to established standards and guidelines. The results obtained show that this agro-industrial residue can be used to produce energy and that the calorific value of the residues used can be improved. The performance of the biomass studied was satisfactory in terms of energy efficiency, in comparison with the previous studies, carried under the same conditions, using sugarcane bagasse and coconut mesocarp. The superior calorific power values found in these briquettes were greater than 16,900 kj/kg, akin to certain wood types and equivalent to sugarcane bagasse briquettes produced using identical methodology.